Islamic Sustainable Development Theories and Their Intellectual Role in Developing Education during Pandemics - Qatawneh, Mohammad Abdelhamid Salem; Al-Naimat, Amal Abdallah (Afkar: Jurnal Akidah dan Pemikiran Islam, 2022)
In Islamic thought, human development in general and sustainable development in education, in particular, is two of the pillars underpinning community development and awareness. These pillars are the mechanisms that would raise and invest in people’s awareness without depleting their energy and efforts, ensuring that wealth and development are perpetuated for generations to come. With revelation and reason as underpinning references, Islamic thought preaches the same pillars and concepts through the five necessities that Islam underlines as a reference for developing people and protecting them against being drained in any form. In view of this, the present paper has sought to review sustainable development in education and the relevant theories in the light of Islamic thought during crises (COVID-19 pandemic as a model). This endeavour is to identify the common ground between general theories of sustainable development in education and the foundations laid by Islamic thought under crises and pandemics based on revelation. The study aimed to solve pending educational issues and look for effective solutions through the sustainable development strategy and the relevant Islamic theories. The study applied the descriptive analytical method to identify and examine these theories. It was concluded that Islamic thought has both depth and inclusiveness, along with a continued momentum to achieve educational development, sustainability, and growth through the foundations it has laid for attaining sustainable development in education.